Hemagglutinin-Specific Non-neutralizing Antibody Is Essential for Protection Provided by Inactivated and Viral-Vectored H7N9 Avian Influenza Vaccines in Chickens - Hu, Zenglei; Zhao, Jiangyan; Zhao, Yiheng; Fan, Xuelian; Hu, Jiao; Shi, Lei; Wang, Xiaoquan; Liu, Xiaowen; Hu, Shunlin; Gu, Min; Cao, Yongzhong; Liu, Xiufan (Frontiers in Veterinary Science, 2020)
Hemagglutination inhibition (HI) and virus neutralization antibody (nAb) do not always correlate with the protection of H7 avian influenza vaccines in mammals and humans. The contribution of different classes of antibodies induced by H7N9 vaccines to protection is poorly characterized in chickens. In this study, antibody responses induced by both inactivated and viral-vectored H7N9 vaccines in chickens were dissected. Chickens immunized with inactivated H7N9 vaccine showed 50% seroconversion rate and low HI and nAb titers at week 3 post immunization. However, inactivated H7N9 vaccine elicited 100% seroconversion rate in terms of high levels of HA-binding IgG antibody determined by ELISA. Despite inducing low levels of nAb, inactivated H7N9 vaccine conferred full protection against H7N9 challenge in chickens and markedly inhibited virus shedding. Similarly, Newcastle disease virus (NDV)-vectored H7N9 vaccine induced marginal HI and nAb titers but high level of IgG antibody against H7N9 virus. In addition, NDV-H7N9 vaccine also provided complete protection against H7N9 challenge. Chicken antisera had a high IgG/VN ratio, indicating that a larger proportion of serum antibodies were non-neutralizing antibody (non-nAb). More importantly, passive transfer challenge experiment showed that non-neutralizing antisera provided partial protection (37.5%) of chickens against H7N9 challenge, without significant difference from that provided by neutralizing antisera. In conclusion, our results suggest that antibodies measured by the traditional HI and virus neutralization assays do not correlate with the protection of inactivated and viral-vectored H7N9 vaccines in chickens, and HA-binding non-nAb also contributes to the protection against H7N9 infection. Total binding antibody can be used as a key correlate to the protection of H7N9 vaccine.